Increasing Lateralized Motor Activity in Younger and Older Adults using Real-time fMRI during Executed Movements. (15th May 2018) - Neyedli, Heather F.; Sampaio-Baptista, Cassandra; Kirkman, Matthew A.; Havard, David; Lührs, Michael; Ramsden, Katie; Flitney, David D.; Clare, Stuart; Goebel, Rainer; Johansen-Berg, Heidi
Highlights: Healthy adults performed movements while receiving neurofeedback from real-time fMRI. Two experiments were performed, one with younger and one with older adults. Neurofeedback (NF) represented the laterality of activation in the motor cortices. The NF groups produced more lateralized activity than the sham group. Abstract: Neurofeedback training involves presenting an individual with a representation of their brain activity and instructing them to alter the activity using the feedback. One potential application of neurofeedback is for patients to alter neural activity to improve function. For example, there is evidence that greater laterality of movement-related activity is associated with better motor outcomes after stroke; so using neurofeedback to increase laterality may provide a novel route for improving outcomes. However, we must demonstrate that individuals can control relevant neurofeedback signals. Here, we performed two proof-of-concept studies, one in younger (median age: 26 years) and one in older healthy volunteers (median age: 67.5 years). The purpose was to determine if participants could manipulate laterality of activity between the motor cortices using real-time fMRI neurofeedback while performing simple hand movements. The younger cohort trained using their left and right hand, the older group trained using their left hand only. In both studies participants in a neurofeedback group were able to achieve more lateralized activity than those in a sham group (younger adults: F (1, 23) = 4.37, p  < 0.05; older adults: F (1, 15) = 9.08, p  < 0.01). Moreover, the younger cohort was able to maintain the lateralized activity for right hand movements once neurofeedback was removed. The older cohort did not maintain lateralized activity upon feedback removal, with the limitation being that they did not train with their right hand. The results provide evidence that neurofeedback can be used with executed movements to promote lateralized brain activity and thus is amenable for testing as a therapeutic intervention for patients following stroke.